Safety and Activity of Programmed Cell Death 1 Versus Programmed Cell Death Ligand 1 Inhibitors for Platinum-Resistant Urothelial Cancer: A Meta-Analysis of Published Clinical Trials - Li, Zaishang; Li, Xueying; Lam, Wayne; Cao, Yabing; Han, Hui; Zhang, Xueqi; Fang, Jiequn; Xiao, Kefeng; Zhou, Fangjian (Frontiers in Oncology, 2021)
Background Programmed death 1/ligand 1 (PD-1/L1) inhibitors have acceptable antitumor activity in patients with platinum-resistant urothelial cancer (UC). However, the reliability and comparability of the antitumor activity, safety profiles and survival outcomes of different immune checkpoint inhibitors are unknown. Our objective was to compare the clinical efficacy and safety of anti–PD-1/PD-L1 therapies in platinum-resistant UC patients. Methods We reviewed the published trials from the PubMed, Embase and Cochrane Library databases up to August 2020. A well-designed mirror principle strategy to screen and pair trial characteristics was used to justify indirect comparisons. The primary end point was the objective response rate (ORR). The safety profile and survival outcomes were also evaluated. The restricted mean survival time (RMST) up to 12 months was calculated. Results Eight studies including 1,666 advanced or metastatic UC patients (1,021 patients with anti–PD-L1 treatment and 645 patients with anti–PD-1 treatment) met the study criteria. The ORRs of anti–PD-1 and PD-L1 therapy were 22% (95% CI, 18%–25%) and 15% (95% CI, 13%–17%) with all studies combined. The proportions of the treated population with a confirmed objective response (I2 = 0; P = 0.966; HR, 1.60; 95% CI, 1.23–2.07; P < 0.001) and disease control (I2 = 30.6%; P = 0.229; HR, 1.35; 95% CI, 1.10–1.66; P = 0.004) were higher with anti–PD-1 therapy than with anti–PD-L1 therapy. The treatment-related adverse events (AEs) (I2 = 78.3%; P = 0.003; OR, 1.09; 95% CI, 0.65–1.84; P = 0.741) and grade 3–5 treatment-related AEs (I2 = 68.5%; P = 0.023; OR, 1.69; 95% CI, 0.95–3.01; P = 0.074) of anti–PD-1 therapy were comparable to those of anti–PD-L1 therapy. The RMST values at the 12-month follow-up were 9.4 months (95% CI,: 8.8–10.0) for anti–PD-1 therapy and 9.3 months (95% CI, 8.8–9.7) for anti–PD-L1 therapy (z = 0.26, P = 0.794). There was no significant difference between patients in the anti–PD-1 and anti–PD-L1 groups (12-month overall survival (OS): 43% versus 42%, P = 0.765. I2 = 0; P = 0.999; HR, 0.95; 95% CI, 0.83–1.09; P = 0.474). Conclusions The results of our systematic comparison suggest that anti–PD-1 therapy exhibits better antitumor activity than anti–PD-L1 therapy, with comparable safety profiles and survival outcomes. These findings may contribute to enhanced treatment awareness in patients with platinum-resistant UC.